Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Pada Standar Proses di MAS YASTI Singkawang - Fitrina Martajasa; Susilawati Susilawati; Deni Irawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the phenomenon of the lag of the Private Islamic Senior High School (MAS) YASTI Singkawang, the second oldest madrasah in the city which has been established since 1991, compared to newer schools that are more popular with the community. The main challenge faced is the small number of students. This condition questions the central role of madrasah principal leadership in improving the quality of education, especially in process standards, to respond to competition. The focus of this research is to examine: (1) the implementation of madrasah principal leadership, (2) supporting and inhibiting factors. This study employed a qualitative method with a field research approach. Data were collected through non-participant observation, in-depth interviews, and documentation studies. Informants in this study included the madrasah principal, teachers, administrative staff, and students. The collected data were analyzed interactively through data reduction, data presentation, and conclusion drawing to ensure the validity of the findings. The results of the study indicate that: (1) The madrasah principal's leadership is implemented collaboratively and participatively, involving all stakeholders in strategic planning and decision-making. (2) Key supporting factors include a conducive madrasah environment and diversified funding sources (BOS and madrasah cooperatives). Meanwhile, inhibiting factors include financial constraints, annual flooding, and a lack of community support and interest. Mitigation strategies were addressed through collaboration with government agencies, universities, and parents/guardians, as well as through simplifying lesson plans to enhance teacher creativity